Biological evaluation of leftover hydrodistilled peels of Citrus sinensis for in-vitro antioxidant and antidiabetic potential - Priti Dongre; Shaily Choudhary; Neeraj Sharma; Chandrashekhar Doifode; Asiya Sheikh (Elsevier, 2024)
Introduction: Citrus sinensis (L.) Osbeck, a member of the Rutaceae family, is medicinal plant high in polyphenols and well-documented in traditional Chinese system of medicine for various significant pharmacological activities. The present study evaluates the antioxidant and antidiabetic potential of leftover hydrodistilled peels of C. sinensis. Method: Crude extract and fractions of Leftover hydrodistilled peels were studied for polyphenolic content. Biological evaluation of crude water extract and fractions at different concentrations was done for in vitro antioxidant DPPH and ABTS assay and antidiabetic α amylase and α-glucosidase inhibition. Result: The estimated phenolic content in crude water extract and chloroform, ethyl acetate, n-butanol and residual fractions were found in a range of 9.26±1.02 - 403±1.3 mg/g equivalent to gallic acid. The flavonoid content was estimated as 3.61±1.34 - 51.4±0.38 mg/g equivalent to quercetin with predominance in ethyl acetate fraction. Antioxidant potential using DPPH and ABTS revealed concentration-dependent activity in ethyl acetate fraction followed by chloroform, crude water extract, residual fraction and n-butanol fraction. Further inhibition of α-glucosidase, and α-amylase indicated the use of hydrodistilled leftover peels as an additional source of antidiabetic compound. Conclusion: The findings of this study indicate that a notable percentage of this waste provided evidence for its utilization scope in the medicinal and nutraceutical sectors and must be recycled to obtain value-added products that can be used to meet population demand.